2007
DOI: 10.1016/j.appet.2006.09.002
|View full text |Cite
|
Sign up to set email alerts
|

How visual images of chocolate affect the craving and guilt of female dieters

Abstract: This study asks whether exposure to images of chocolate induces cravings and guilty feelings in females. A further aim was to examine whether these effects are heightened in the case of dieters. The participants, 85 females, saw a series of enticing media images, either of chocolate or of non-food products. Two thirds of the sample were dieting or had dieted in the past; 15% had been on seven or more diets. After viewing the images all participants completed the Attitudes to Chocolate Questionnaire (ACQ) (Bent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 29 publications
1
24
0
1
Order By: Relevance
“…Chocolate has a strong effect on mood, generally increasing pleasant feelings and reducing tension (Osman and Sobal, 2006; Parker et al, 2006b; Cartwright et al, 2007; Fletcher et al, 2007). Chocolate contains psychoactive chemicals such as andamines that stimulate the brain and result in good mood (Ottley, 2000).…”
Section: Central Nervous System In Regulation Of Mood Food and Obesitymentioning
confidence: 99%
“…Chocolate has a strong effect on mood, generally increasing pleasant feelings and reducing tension (Osman and Sobal, 2006; Parker et al, 2006b; Cartwright et al, 2007; Fletcher et al, 2007). Chocolate contains psychoactive chemicals such as andamines that stimulate the brain and result in good mood (Ottley, 2000).…”
Section: Central Nervous System In Regulation Of Mood Food and Obesitymentioning
confidence: 99%
“…However, an alternative conceptualization might emphasize the qualitative aspect of dietary restraint, namely the attempted abstinence of binge eaters from 'forbidden,' palatable foods (Kales, 1990;Knight and Boland, 1989;Fletcher et al, 2007;Mitchell and Brunstrom, 2005;Gonzalez and Vitousek, 2004;Stirling and Yeomans 2004;Corwin, 2006;Corwin and Buda-Levin, 2004). Binge eaters restrict their intake of 'forbidden' foods to the point that 'relapse' intake is limited to very brief, often ritualized, binge episodes, perhaps precipitated by mild energy restriction.…”
Section: Introductionmentioning
confidence: 99%
“…The resulting weight gain often causes more psychological and physical damage, and motivates many people to blame themselves for the failure and once again turn to the questionable diet industry in subsequent attempts to lose weight. Supporting this phenomenon are the results of Fletcher, Pine, Woodbridge, and Nash (2007) who found that of the 67 percent of women who had previously been on a diet, 68 percent had tried to lose weight between one to four times, 16 percent between four to seven times, and 15 percent had tried to lose weight more than seven times. The modal age group for participants in this study was 16 -20 years.…”
Section: Implications For Preventionmentioning
confidence: 92%